Variation in which key motivational and academic resources relate to academic performance disparities across introductory college courses - Lorraine Blatt; Christian D. Schunn; Elizabeth Votruba-Drzal; Benjamin Margolin Rottman (SpringerOpen, 2020)
Abstract Background Differences in post-secondary academic outcomes along dimensions of gender, race/ethnicity, and socioeconomic status are a major concern. Few studies have considered differences in patterns of academic outcomes and underlying mechanisms driving disparities across different STEM disciplines. Using data from about 4000 undergraduates in introductory STEM courses at a large, urban university in the eastern United States, this study examines how differences in course grades by gender, race/ethnicity, and parent education vary in introductory chemistry, physics, and psychology courses. In addition, structural equation modeling techniques examine whether academic resources and discipline-specific motivational attitudes are important mediators of demographic differences in course grades. Results This study finds that women have higher course grades than men on average in psychology, and men have marginally higher grades than women in physics. In addition, students whose race/ethnicity is represented or overrepresented in these courses (students who are White and or Asian) have higher course grades in chemistry and physics and marginally higher grades in psychology on average compared with underrepresented students (who are Black, Latinx, Native American, Pacific Islander, and or other racial/ethnic backgrounds). Further, first-generation college students have lower course grades in physics and psychology on average than students with a college-educated parent. The largest average differences in course performance are about half a full letter grade (e.g., the difference between a B and an A−). This study also finds that some demographic differences in physics and chemistry performance are linked to math resources whereas some disparities in psychology are more related to verbal resources. In addition, the results suggest discipline-specific self-efficacy is a motivational attitude associated with course performance in chemistry, physics, and psychology, while discipline-specific interest is only relevant in chemistry. Conclusions Overall, the findings emphasize that there are demographic differences in post-secondary course performance on average, and academic resources and motivational attitudes help explain these differences. Importantly, the specific findings differ across chemistry, physics, and psychology. Understanding these pathways and how they are similar and different across disciplines within STEM is crucial for developing interventions aimed at attenuating disparities in post-secondary academic outcomes.